2017
DOI: 10.1080/1059924x.2017.1283279
|View full text |Cite
|
Sign up to set email alerts
|

Financial Considerations for Health and Safety in the Australian Dairy Industry

Abstract: Despite data limitations, there is a compelling financial case to increase strategic investments into work health and safety by dairy farmers in Australia. Increased investment has the potential to not only minimize the burden of injury and costs to dairy farmers, but will also significantly reduce the devastating impacts that these incidents have on individuals, their families and communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Investments in safety often compete with investments to increase productivity and general family needs. Typically, farmers choose lower-order, cheaper safety options [ 93 ]. Saluja and colleagues [ 2 ] explained that parents acknowledge there are changes they can implement to enhance their child’s safety but are faced with limited economic and practical resources.…”
Section: Resultsmentioning
confidence: 99%
“…Investments in safety often compete with investments to increase productivity and general family needs. Typically, farmers choose lower-order, cheaper safety options [ 93 ]. Saluja and colleagues [ 2 ] explained that parents acknowledge there are changes they can implement to enhance their child’s safety but are faced with limited economic and practical resources.…”
Section: Resultsmentioning
confidence: 99%
“…22,23 A recent pilot study in the Australian dairy sector indicated that small investments that are well targeted can have significant positive safety and financial benefits. 24 Whether assessed from the broader industry or from an individual farm business perspective, it is often remarked that people are the most important asset that a business can have and that safety is a number one priority. 25 Notwithstanding such rhetoric, the actual investments in health and safety stand in contrast to these assertions.…”
Section: Discussionmentioning
confidence: 99%